Performance study and efficiency improvement of Hybrid Electric System dedicated to transport application. (27th April 2017) - Sami, Ben Slama; Sihem, Nasri; Zafar, Bassam; Adnane, Cherif
Abstract: A Proton Exchange Membrane Fuel Cell (PEMFC) powered Hybrid Electric System (HES) is one of an appreciating research issue for the future due to its high efficiency and capability to use hydrogen as a fuel. The PEMFC cannot sufficiently meet sustained load demands in some cases. For that, to compensate this problem incorporating the slow transient response of the PEMFC, Ultra-capacitors (UCaps) are potential candidates for a solution in this aspect. An adequate Energy management System (EMS) is one essential objective of the researches in this area. Hence, this paper proposed an efficient dynamic model using an energy storage system with the sufficient power capacity to keep the smooth operation of the system. To satisfy the load requirements and optimize the active power flow between hybrid power sources for different modes, the EMS was proposed. This latter was appreciated for its capacity to serve the required power through effective utilization of the PEMFC and UCap. To maximize the system efficiency, the functioning of the system is depending on the decision making and the control of all the system component states. The HES and the control approach are made using Matlab/Simulink environment, from which, the obtained results indicate the reliability and the effectiveness desirability of the HES and its proposed energy management strategy. Highlights: Dynamic study of Hybrid Electric System (HES) comprising PEMFC and UCap. Applying of an efficient Energy Management Strategy (EMS) to improve all system performances. HES efficiency study and improvement. Load profile treating transport application.